In the Midst of the City: An Exploration of Conflict and Identity in the Rivers of London novels of Ben Aaronovitch - Burn, Jo Anna (Auckland University of Technology, 2025)
This thesis is an exploration of Ben Aaronovitch’s Rivers of London urban fantasy crime novels, with a focus on how the representation of the city reflects socio-political currents in contemporary Britain. Set-in present-day London, the books discuss conflict, identity and the role of the police whilst also exploring how social justice manifests in the twenty first century. Specific themes include friction between urban and rural communities, changing demographics and ethnic tensions, the role of London versus the provinces, class divisions, marginalisation of the poor and insecurely housed and what it means to be a ‘good’ citizen in contemporary Britian. Eco-critical elements examine degradation of the built environment, architectural responses to community need, and the intersection of the city with the natural world including flood mitigation and the plight of urban wildlife. The police response to security threats is contextualised by underlying tensions engendered by past trauma and terrorist events, and the role of the mob in protesting social inequalities. The impact of austerity policies on eroding the effectiveness of the police, and media commentary on geopolitical changes within the British state are also examined. There has hitherto been limited scholarly attention on how post-Global Financial Crisis (GFC) political and social policy in Britain have manifested in contemporary fantasy literature, and in the work of Aaronovitch in particular, and this thesis goes some way towards filling that gap. The major mythological strand running through the series is embodied in the image of the divided river Thames. Jungian myth criticism provides a tool to interpret the mythopoeic and allegorical elements in the corpus as Aaronovitch expands the tutelary gods of the Thames to incorporate an African river goddess alongside traditional guardian Father Thames. This reimagining of the Thames origin myth more accurately reflects London’s history as a port, a hub for trade and immigration, and how these have changed the complexion of British society. Aaronovitch’s vision of tolerance and plurality provides a contrast to dystopian imaginations of the city which are common in urban fantasy. His diverse pantheon of river gods and goddesses, and other mythical characters such as Mr Punch provide the opportunity for a Jungian synthesis of disparate elements representing the strengths of traditional and contemporary Britain. Opposing forces are mediated by the central figure of Constable Peter Grant who undergoes his own process of synthesis as the series progresses. The books are a celebration of diversity, tolerance and psychological growth as well as a warning against social dysfunction, economic disparities and the perils of failing to adapt to change.